2010
DOI: 10.3390/s100706377
|View full text |Cite
|
Sign up to set email alerts
|

A High Sensitivity Micro Format Chemiluminescence Enzyme Inhibition Assay for Determination of Hg(II)

Abstract: A highly sensitive and specific enzyme inhibition assay based on alcohol oxidase (AlOx) and horseradish peroxidase (HRP) for determination of mercury Hg(II) in water samples has been presented. This article describes the optimization and miniaturization of an enzymatic assay using a chemiluminescence reaction. The analytical performance and detection limit for determination of Hg(II) was optimized in 96 well plates and further extended to 384 well plates with a 10-fold reduction in assay volume. Inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…The inhibition of carbonic anhydrase by heavy metalsspecifically Pb, Cu and Hg has been reported (Ek _ Inc _ et al, 2007). The biosensors for Hg 21 detection developed using the inhibition of alcohol oxidase (Deshpande et al, 2010) showed great amplification of the chemiluminescent signal. The specificity was also tested with Pb and Cd and the developed enzyme biosensor revealed a LOD of 1 pg mL À1 and good specificity for Hg 21 .…”
Section: Chemiluminescent Methodsmentioning
confidence: 99%
“…The inhibition of carbonic anhydrase by heavy metalsspecifically Pb, Cu and Hg has been reported (Ek _ Inc _ et al, 2007). The biosensors for Hg 21 detection developed using the inhibition of alcohol oxidase (Deshpande et al, 2010) showed great amplification of the chemiluminescent signal. The specificity was also tested with Pb and Cd and the developed enzyme biosensor revealed a LOD of 1 pg mL À1 and good specificity for Hg 21 .…”
Section: Chemiluminescent Methodsmentioning
confidence: 99%
“…The enzymatic inhibition results in a CL suppression that is analyte concentration dependent. Though, in a previous work, Deshpande et al [41], exploiting a two enzyme based (i.e., alcohol oxidase (AlOx) and HRP) inhibition assay for single HM ion determination, showed a lower LOD (1 pg/mL) for Hg 2+ ions.…”
Section: Biosensing Methodsmentioning
confidence: 99%
“…Many of these tests and devices are being developed to address needs other than security (e.g., water quality issues such as arsenic in well water); however, these tests may also serve in enhanced water security. Examples include microfluidic sensors that can detect low concentrations of contaminants such as lead (Chang et al, 2005), a biosensor used to detect arsenic in drinking water (de Mora et al, 2011), micro-chemiluminescence enzyme tests for mercury in drinking water (Deshpande et al, 2010), a self-powered enzyme biofuel cell on a microchip for cyanide detection (Deng et al, 2010), and a biosensor for arsenic detection that is inexpensive and field deployable (Joshi et al, 2009). Advancements have also been made in testing for lead in drinking water (Wang et al, 2001).…”
Section: Novel Detection Technologymentioning
confidence: 98%